POLA KOMUNIKASI DAKWAH KOMUNITAS MUSLIM DALAM MENJAGA HARMONI SOSIAL - Yohandi Yohandi; Khusna Amal (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2019)
Da'wah is not only understood by the meaning but also as a science, but must be understood as a noble behavior to create a happy life both in the world and hereafter. Thus, da'wah has moral responsibility to fulfill the intended purpose. Because da'wah is the process of conveying religious messages, da'wah cannot be separated from the communication process. In other words, preaching must pay attention to the principles of communication, especially in terms of patterns of inter-cultural communication, especially when the mission is delivered in the midst of non-Muslim communities. This paper has three main issues, are: 1) the concept of understanding the importance of maintaining harmony; 2) the da'wah strategy in the midst of the Hindu community, so that it does not adversely affect social harmony; and 3) the pattern of relations between Muslim and Hindu communities in maintaining social harmony. These three issues are the focus of writing this article. This paper gives the message that survival while maintaining harmony in differences is an obligation. Religious differences should not be a barrier to staying together, socializing and side by side. Because in essence every religion craves peace and harmony in the life of the nation and state. Keywords: da'wah communication, Muslim community, social harmony